2011
DOI: 10.1002/jmv.21990
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of norovirus GII‐4 antibodies in Finnish children

Abstract: Noroviruses (NoVs) are the second most common cause of viral gastroenteritis after rotavirus in children. NoV genotype GII‐4 has emerged as the major type not only in outbreaks of NoV gastroenteritis but also endemic gastroenteritis among infants and young children worldwide. Using baculovirus‐insect cell system virus‐like particles (VLPs) of NoV genotype GII‐4 and an uncommon genotype GII‐12 were produced. These VLPs were used in enzyme‐linked immunosorbent assays (ELISA) for detection of NoV‐specific immunog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
63
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 35 publications
(55 reference statements)
11
63
1
Order By: Relevance
“…Importantly, exposure to the natural infection increases with time as reflected by the accumulation of antibodies. 52 Similar results are reported in other developing countries whereby constant exposure to NoV infections in India has been described across all age groups. 53 The authors suggested that NoV infections occur in children and infants with reinfections being more common as compared to other developed settings (specifically the United Kingdom).…”
Section: Viral Shedding Natural Infection With Nov and Seroprotectionsupporting
confidence: 86%
“…Importantly, exposure to the natural infection increases with time as reflected by the accumulation of antibodies. 52 Similar results are reported in other developing countries whereby constant exposure to NoV infections in India has been described across all age groups. 53 The authors suggested that NoV infections occur in children and infants with reinfections being more common as compared to other developed settings (specifically the United Kingdom).…”
Section: Viral Shedding Natural Infection With Nov and Seroprotectionsupporting
confidence: 86%
“…Maximum VLP binding was determined in wells containing VLPs without serum. Bound VLPs were detected with human NoV antiserum (29) and an anti-human IgG-HRP secondary antibody, followed by OPD substrate as described above. OD readings were determined spectrophotometrically at 490 nm with a microplate reader.…”
Section: Vlpmentioning
confidence: 99%
“…GII.4 strain NoVs have an exceptionally broad HBGA binding repertoire and high transmissibility (2), explaining the predominance of GII.4 NoV infections worldwide (28). The quantity of genotype-specific antibodies that can block the binding of NoV VLP to the HBGA has been shown to increase remarkably after NoV infection or NoV VLP immunization in humans (18,19,29,30). Prechallenge levels of blocking antibodies in human serum have been shown to positively correlate with the protection of both NoV infection and illness, and it is generally accepted that especially blocking antibodies in serum play a substantive role in protection from NoV infection (18,31).…”
mentioning
confidence: 99%
“…The virus is spread by contaminated food and water and from person to person via the faecal-oral pathway and can be further transmitted to food and food contact surfaces by virus-contaminated hands [9,10]. Because the biological characterisation of human NoV has been hampered by the lack of an appropriate cell culture system and animal model for the propagation of the virus, virus-like particles (VLPs) have been used extensively to study NoV structure and stability, host-cell interactions, and as a tool in diagnostic serological assays [10][11][12][13]. Structural studies have shown that the noroviral capsid is composed almost entirely of the 58 kDa VP1 capsid protein [13], which self-assembles into empty capsids called virus-like particles (VLPs) when expressed recombinantly in insect cells or in yeast [14].…”
Section: Introductionmentioning
confidence: 99%